An analysis of the factors affecting mobile commerce adoption in developing countries: Towards an integrated model. Issue 3 (2nd September 2019) - Tarhini, Ali; Alalwan, Ali Abdallah; Shammout, Ahmad Bahjat; Al-Badi, Ali
Abstract : Purpose: This study aims to investigate the factors that may hinder or facilitate consumers' adoption of mobile-commerce (m-commerce) activities in the context of developing countries exemplified here by Oman. Design/methodology/approach: A conceptual model was developed through integrating factors from UTAUT2 (performance expectancy, expectancy effort, social influence, facilitating conditions, hedonic motivation, price value, habit and self-efficacy) and SERVQUAL (system quality, service quality and information quality). Data were collected from 530 Omani m-commerce users through a cross-sectional survey. Findings: The results of the structural equation modelling showed that consumers' behavioural intention (BI) towards m-commerce adoption was significantly influenced by information quality, habit, performance expectancy, trust, hedonic motivation, service quality, price value and facilitating conditions, in their order of influencing strength, and explained 65.5 per cent of the variance in BI. Unexpectedly, effort expectancy, social influence, self-efficacy and system quality had no significant effect on BI. Practical implications: This study will explain the currently relatively low penetration rate of m-commerce adoption in Oman, which will help local m-commerce businesses to develop the right organizational strategies, especially related to marketing strategies and developing mobile applications, which will draw the attention of many users. Originality/value: This is one of the few studies that integrates UTAUT2 with SERVQUAL and tests the proposed model in non-Western cultural contexts. Specifically, in contrast to previous studies, diversity of individuals' acceptance behaviour is examined in Oman.